1983
DOI: 10.1002/j.1460-2075.1983.tb01644.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial rescue of dorsal , a maternal effect mutation affecting the dorso-ventral pattern of the Drosophila embryo, by the injection of wild-type cytoplasm

Abstract: Mutant alleles at the maternal effect locus dorsal cause a dorsalization of the Drosophila embryo. In extreme mutants, the embryos develop exclusively structures which derive from the dorsal‐most region in normal eggs, in less strong phenotypes in addition to dorsal structures, structures normally derived from a dorso‐lateral to lateral egg region are formed. Injection of cytoplasm from wild‐type embryos into mutant embryos partially restores the dorso‐ventral pattern in that injected embryos develop additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 7 publications
(3 reference statements)
0
9
0
Order By: Relevance
“…Previous studies had demonstrated that the transplanted cytoplasm of wild‐type embryos is capable of rescuing the dorsalized phenotypes of embryos derived from mothers mutant for Toll , snake , tube , easter , pelle and, to a lesser extent, dorsal. With the exception of Toll , the DV axis of these embryos is invariably oriented normally with respect to the intrinsic DV polarity of the eggshell. In contrast, in rescued embryos maternally mutant for Toll , the polarity of the DV axis is determined by the site of injection, which develops as the most ventral part of the rescued pattern .…”
Section: The Dorsal Group Genesmentioning
confidence: 99%
“…Previous studies had demonstrated that the transplanted cytoplasm of wild‐type embryos is capable of rescuing the dorsalized phenotypes of embryos derived from mothers mutant for Toll , snake , tube , easter , pelle and, to a lesser extent, dorsal. With the exception of Toll , the DV axis of these embryos is invariably oriented normally with respect to the intrinsic DV polarity of the eggshell. In contrast, in rescued embryos maternally mutant for Toll , the polarity of the DV axis is determined by the site of injection, which develops as the most ventral part of the rescued pattern .…”
Section: The Dorsal Group Genesmentioning
confidence: 99%
“…2015). DL is deposited maternally and functions as a master regulator in specifying the DV axis (Santamaria and Nüsslein-Volhard 1983; Roth et al . 1989; Ratnaparkhi and Courey 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The phenotypic series suggested a morphogen gradient with a maximum at the ventral side of the egg determining the dorsoventral axis (Figure 3D) [7][8][9]. Pedro Santamaria later demonstrated that transplantation of wild-type cytoplasm could indeed partially rescue the mutant phenotype [10]. By that time, however, the advent of gene technology and germ line transformation in Drosophila meant that the road to the gene product would be via cloning the gene and not via protein purification.…”
Section: Open Accessmentioning
confidence: 99%
“…The results of the transplantation experiment singled out two genes, dorsal and Toll. In the case of dorsal, cytoplasm from the ventral side of older preblastoderm embryos is more active than that from the dorsal side, and the cytoplasm has to be delivered at the ventral side to be active [10]. Supported by the strong dosage dependence, dorsal appeared the best candidate for encoding the morphogen determining the dorsoventral axis.…”
Section: Trends In Geneticsmentioning
confidence: 99%